Primary empty sella syndrome presenting as adrenal insufficiency and without raised intracranial tension - Gupta, Ishank; Panchalwar, Vinay; Chabra, Aman (International Journal of Research in Medical Sciences, 2022)
Empty sella syndrome (ESS) based on pathophysiology can be either primary empty sella syndrome (PES) or secondary empty sella syndrome (SES). Patients of PES have no known pituitary pathology and have varying degrees of pituitary gland flattening. We present a 65-year-old female who came with complaints of generalised swelling over the body, generalised weakness, altered sensorium and low-grade fever. Patient had history of ischaemic heart disease 3 years back without any other known co-morbidities. Patient presented in hypoglycaemia and hypotension with facial puffiness and oedema feet with basal crepitations indicating fluid overload state. Patient was stabilised and evaluated. Patient was found to have hyponatremia and urinary tract Infection and associated acute kidney injury. Patient’s morning cortisol and adrenocorticotropic hormone (ACTH) levels were also low with associated low insulin-like growth factor 1 (IGF-1) and normal thyroid stimulating hormone (TSH) levels but low T3 and low T4 levels. Patient’s magnetic resonance imaging (MRI) brain was done which was suggestive of PES. The cause of empty sella remained unclear but the adrenal insufficiency was treated with hydrocortisone and the patient became asymptomatic and was discharged subsequently.